Influence Return on Equity (ROE), and Net Profit Margin (NPM) Against Return Shares of Food and Beverage Sub-Sector Companies on the Indonesian Stock Exchange Period 2022-2023 - Joni Devitra (Journal Research of Social Science, Economics, and Management, 2025)
Focusing on the 2022–2023 period, this research investigates the effect of "Return on Equity (ROE) and Net Profit Margin (NPM)' on the stock returns of companies in Indonesia’s food and beverage sector. The study uses a quantitative method, analyzing financial report data obtained through census sampling and tested using SPSS 29. Results show that both ROE and NPM significantly and positively influence stock returns. Furthermore, combined analysis shows that ROE and NPM simultaneously influence stock returns significantly, explaining 44.6% of the variation in stock returns. The findings underscore that profitability metrics significantly influence investor choices and the market's behavior within this sector. The study implies that investors and company managers should closely monitor these financial ratios for better capital allocation and strategic planning. Policymakers may also benefit from these insights to promote market transparency and stability. Future research is recommended to include additional financial indicators and external factors like market volatility to provide a more comprehensive understanding of stock return determinants in emerging markets.